ESTIMASI PENERIMAAN DANA BAGI HASIL PAJAK EKSPOR CRUDE PALM OIL (CPO) DAN PENGARUHNYA TERHADAP PENDAPATAN DAERAH DI KALIMANTAN BARAT (PROYEKSI 2014 – 2025) - RADU SURANTA KARO SEKALI, B61112055 (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT The title of this research is the Estimated Revenue Sharing Fund CPO Export Tax and its Effect on Regional Income in West Kalimantan ( Projected years 2014-2025 ) . Research Objectives are : 1 ) Calculate the result of the acquisition of funds for the CPO export tax . 2 ) Test the contribution of revenue -sharing funds to the CPO export tax revenues West Kalimantan . Government of West Kalimantan through Peraturada 1 / 1995 on the Provincial Spatial Plan ( RTRWP ) West Kalimantan , oil palm proclaimed as one of the sources of local revenue . In West Kalimantan RTRWP 1995 potentially exposed land area of ​​5.2577 million ha plantation will be handed over to the 164 companies amounted to 2,500,000 ha plantation ( 48 % of potential land area ) to oil palm plantations . Form of research is descriptive quantitative trying noticed revenues from export taxes in West Kalimantan . Before performing the calculation of the contribution of funds to the CPO export tax revenue to income areas in West Kalimantan conducted prior projection CPO export volume , Value Exchange , Rates CPO exports of years 2014-2025setelah the CPO export tax calculation . CPO export volume data using exponential 2000-2013diproyeksi year , while the value of the exchange rate and the rates in the CPO export projection by using the method of Arima ( Jenkin Box ) From these results obtained CPO export tax for the year 2014-2025 amounting to Rp . 3,560,328,866,925 . If the export port in West Kalimantan built the local government of West Kalimantan will be an additional source of local revenue -sharing funds CPO export tax of Rp . 574 725 562 414 . Based on the results of testing the effectiveness of revenue-sharing CPO export tax on the income of 48.88 % . From the results of the test figures show both criteria so that funds for this result is very potential to be a source of income for the region of West Kalimantan . Keywords : Port Exports , Revenue Sharing , and Revenue